THE PAYMENT LATER SYSTEM, FINANCIAL LITERACY, HEDONISM, AND FEAR OF MISSING OUT TO CONSUMPTIVE BEHAVIOR GEN-Z - Anisa Nur Savitri; Muhamad Safiq; Widyahayu Warmmeswara Kusumastati (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2026)
This study aims to examine the influence of payment systems, financial literacy, a hedonistic lifestyle, and Fear of Missing Out (FOMO) on Gen-Z consumer behavior. The researcher was motivated by the phenomenon or information that Indonesians are the largest internet users in Southeast Asia. This study used a sample of 200 people collected from users of internet-based payment systems (Paylater), specifically Gen-Z. The sampling strategy used was purposive sampling, with Gen-Z being aged between 18 and 28 years and using internet-based payment systems. The survey data consisted of a questionnaire with 38 prepared questions that was delivered online using the Google Forms platform. The questionnaire responses were measured using a 5-point Likert scale, with 1 representing Strongly Disagree and 5 representing Strongly Agree. In data analysis, the researcher used SmartPLS. The results showed that internet-based payments (Paylater) influence consumptive behavior of Gen-Z. Second, financial literacy has a significant positive influence on Gen-Z consumer behavior. Next, a hedonistic lifestyle has a positive effect on Gen-Z consumer behavior. Finally, Fear of Missing Out (FOMO) has a positive effect on Gen-Z consumptive behavior.